Effect of heat-moisture treatment on the structural, physicochemical, and rheological characteristics of arrowroot starch - Pepe, Larissa S. [UNESP]; Moraes, Jaqueline [UNESP]; Albano, Kivia M. [UNESP]; Telis, Vânia Rn [UNESP]; Franco, Célia Ml [UNESP] (Food Science And Technology International, 2015)
The effect of heat-moisture treatment on structural, physicochemical, and rheological characteristics of arrowroot starch was investigated. Heat-moisture treatment was performed with starch samples conditioned to 28% moisture at 100℃ for 2, 4, 8, and 16 h. Structural and physicochemical characterization of native and modified starches, as well as rheological assays with gels of native and 4 h modified starches subjected to acid and sterilization stresses were performed. Arrowroot starch had 23.1% of amylose and a CA-type crystalline pattern that changed over the treatment time to A-type. Modified starches had higher pasting temperature and lower peak viscosity while breakdown viscosity practically disappeared, independently of the treatment time. Gelatinization temperature and crystallinity increased, while enthalpy, swelling power, and solubility decreased with the treatment. Gels from modified starches, independently of the stress conditions, were found to have more stable apparent viscosities and higher G' and G″ than gels from native starch. Heat-moisture treatment caused a reorganization of starch chains that increased molecular interactions. This increase resulted in higher paste stability and strengthened gels that showed higher resistance to shearing and heat, even after acid or sterilization conditions. A treatment time of 4 h was enough to deeply changing the physicochemical properties of starch.
Keywords: Starch; Physical properties; Rheology; Viscosity